Productive performance of grazing lambs supplemented with fermented coffee pulp - Aguirre, L. A.; Gutiérrez, D.; Rodríguez, Zoraya; Chuquirima, D.; Abad, R. (Cuban Journal of Agricultural Science, 2019)
To study the productive performance of grazing lambs, supplemented with fermented coffee pulp, an experiment was carried out for 90 d. Twenty creole entire lambs were used, with initial live weight of 20.34 ± 1.64 kg (9.56 ± 0.58 kg LW0.75), between 5-6 months of age, divided into two groups, according to a completely randomized design. The treatments consisted of: T1) without supplementation (control) and T2) with supplement (fermented coffee pulp, sugarcane, corn, soybean, alfalfa meal and mineral salts). Both groups had free access to grazing for 8 h daily. The supplement was offered at a rate of 11 g kg LW-1, on dry basis, on a single occasion (4:00 pm) during the enclosure. The results showed higher average daily weight gain (74.11 g d-1, P <0.0001), hot carcass yield (47 %, P = 0.0033), dry matter intake (89.01 g kg LW0.75, P <0.0001) and food conversion (12.9, P <0.0001) in treatment two. It was observed that the average daily gain is related to dry matter intake (r = 0.90, P <0.0001), energy intake (r = 0.90, P <0.0001) and protein intake (r = 0.94, P <0.0001). Therefore, the the yield of hot carcass is determined by the dry matter intake and the total weight gain (R2 = 0.69, P = 0.0162). It is concluded that the use of supplement with 30 % of fermented coffee pulp improves the productive performance of grazing creole lambs, so it can be an interesting alternative for these production systems, especially during the dry season, where there is a marked forage shortage. Key words: creole sheep, grazing, supplement, daily average gain, carcass yield.